Totally synthetic microperoxidase-11. Issue 5 (23rd May 2018) - Tanabe, Junichi; Nakano, Koji; Hirata, Ryutaro; Himeno, Toshiki; Ishimatsu, Ryoichi; Imato, Toshihiko; Okabe, Hirotaka; Matsuda, Naoki
Abstract : A totally synthetic microperoxidase-11 (MP-11) is reported. Accordingly, the undecapeptide (VQKCAQCHTVE) was synthesized by solid-phase peptide synthesis followed by the thiol-ene click reaction with haemin for reconstitution. High-speed atomic force microscopy measurement conducted in water confirmed the protein reconstitution by visualizing the morphological differences as animated molecular images. The synthetic MP-11 showed a considerable magnitude of catalytic activity (27%) against the natural MP-11 in the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine by hydrogen peroxide, whereas it showed very low (2.7%) activity of a synthetic variant with a point mutation (VQKCAQC M TVE, H8M). Slab waveguide spectroscopic measurements revealed that the ferrous/ferric redox reaction occurred by the direct electron transfer with specific spectral changes. Indeed, if hydrogen peroxide existed in the solution phase, the peroxidase-modified electrode showed catalytic current–voltage behaviour regardless of whether it was prepared using natural MP-11 or the synthetic MP-11. If a substrate recycling reaction was assumed, computer simulation well reproduced the experimental curves to give a global set of electrocatalytic reaction parameters. In any of the experiments, the synthetic MP-11 and natural MP-11 gave almost identical results. Our approach will be a convenient means of preparing MP-11, as well as its mutants, that does not rely on nature.